Environmental effects of Arctic oil spills and spill response technologies, introduction to a 5 year joint industry effort. (February 2019) - Camus, Lionel; Smit, Mathijs G.D.
Abstract: With the level of industrial activities increasing in Arctic areas it is crucial to assure that dedicated oil spill response capabilities and strategies are available for deployment in this region. To further build on existing research and improve technologies and methodologies for Arctic oil spill response, nine oil and gas companies established the Arctic Response Technology Joint Industry Program (ART-JIP) in 2012 with the goal to advance Arctic oil spill response strategies and equipment as well as to increase understanding of potential impacts of oil on the Arctic marine environment. As part of the environmental effects research program of the ART-JIP a comprehensive review of the environmental impacts arising from both the oil spill itself and the countermeasures activities was executed. A number of research activities were identified to improve the knowledge base for using a Net Environmental Benefit Analysis (NEBA) in the Arctic. As a follow-up of the review modelling-, laboratory- and field studies were conducted. The data collected from the review and the additional studies have been organized in an information tool to support tool Arctic NEBA. Results from the studies have improved the understanding of what happens to oil once frozen into ice, how the microbe communities are reacting to oil in ice and what the exposure potential and effects are on the marine organisms that live in association with the ice. This output from the ART-JIP will help managing oil spill impacts and will assist in the definition of a response strategy that minimizes effects to the environment.